Mercury bioaccumulation in the Egyptian mongoose (Herpestes ichneumon): Geographical, tissue, gender and age differences - Rodrigues, S.
The main purpose of this study was to evaluate the mercury (Hg) bioaccumulation in the Egyptian mongoose (Herpestes ichneumon), a terrestrial predator species with an essential role in the Iberian ecosystems food chain. Differences between males and females and the effect of age in mercury body burdens were studied, as well as the geographical distribution of mercury in tissues ofthe studied species.Totalmercury (T-Hg)was determined in muscle, liver, lungs, heart, spleen, kidneys, blood, brain, fat and pelage of the Egyptian mongoose from 14 locations, encompassing the distribution range of the element in the species. In order to study differences between ages, males and females, 20 individualsfromonesamplinglocationwereanalysed.Total mercury concentrations ranged between 0.01 and 13 μgg −1 (dry weight (dw)) and followed the order from the least to the most contaminated: fat<brain< lungs<heart<spleen<muscle<kidneys<liver<pelage <blood. Differences between males and females were only significant for muscle and pelage mercury levels, suggesting uptake rates and metabolic processes to be similarbetweengenders.Despiteasimilaraccumulation patternwithagebetweenmalesandfemales,differences between ages were significant only for females, as a result of a higher range of male mercury body burdens. Organic mercury (O-Hg) was analysed in muscle and liver, and its percentage ranged from 83 to 96 %, reflecting the high trophic level of the species. None of the observed mercury levels reached the lethal or toxic values established for terrestrial predators (20 to 100 μgg −1 wet weight), suggesting that despite its predatory position in terrestrial food webs, the risk of mercury associated toxicity is low.